Multiple lichen planus‐like keratoses: Lichenoid drug eruption simulant and under‐recognised cause of pruritic eruptions in the elderly. (5th March 2015) - Pitney, Lucy; Weedon, David; Pitney, Michael
Abstract: We present six cases of multiple eruptive lichen planus‐like keratoses (LPLK), occurring in older individuals predominately confined to previously solar exposed areas. Diagnosis was often confounded by the frequent histological reporting of 'lichenoid drug reaction' (LDR), despite many of the patients being unmedicated. We review the literature regarding eruptive LPLK and reflect on their etiology, clinical aspects, management and importantly their clinicopathological differentiation from LDR.